Digital Transformation of Public Services: An Analysis of the Effectiveness of Online Services at the Local Government Level - Indar, Indra Nur; Razi, Dien Fakhrur; Atmansyah, Lutfi; Yani, Andi Ahmad; Ismail, Nuralamsyah (Journal of Digital Sociohumanities, 2024)
This study examines the effectiveness of online services at the local level (District) Office which sees the existence of E-Gov encouraging the government to create good governance in providing information needs and transparency to the community. The renewal of public services in the reform era is the main focus of the government as an effort to realize good governance. The research method used is qualitative. This research uses the concept proposed by Pedrosa et al (2022) which uses eight indicators of the effectiveness of digital public services: ease of use, usefulness, simplicity, reliability, availability, understandable, consistent, and fast. The results showed that online-based services at the agency were effective in several aspects, such as trust and availability, but there were still shortcomings in the aspects of simplicity and consistency. Online services are considered easy to find through familiar channels and have a fast response, less than an hour. Nevertheless, the implementation of online service SOPs still needs to be improved. This study concludes that online services have become an attractive asset in the effort to transform the digitalization of public services.